A case study of international notarization cooperation in private international law: a notarized power of attorney signed by a French citizen to accept a real estate gift - Zhang, Zheng; Cai, Yong (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This case reflects how Chinese notaries and French notaries cooperate to provide highquality legal services for the parties in the background of global epidemic.
Keywords: Private international law; international notarization cooperation; pandemic; France